2008
DOI: 10.1080/02699050801992824
|View full text |Cite
|
Sign up to set email alerts
|

Use of the emotional Stroop to assess psychological trauma following traumatic brain injury

Abstract: Findings suggested that patients, both with and without explicit recall for an RTA, responded similarly on a task involving implicit memory for trauma. Possible implications for ASD and Post-traumatic Stress Disorder are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In turn Coates (2008) verified the hypothesis concerning the influence of implicit memory on the interference effect in the Stroop test. For this purpose he selected as his research groups the following: (a) persons who had been involved in a road traffic accident, suffered brain damage, and did not remember the accident (15 persons); (b) persons who had been involved in a road traffic accident and retained a memory of the event (13 persons); and, as a control group, (c) patients of an orthopedic ward (15 persons).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In turn Coates (2008) verified the hypothesis concerning the influence of implicit memory on the interference effect in the Stroop test. For this purpose he selected as his research groups the following: (a) persons who had been involved in a road traffic accident, suffered brain damage, and did not remember the accident (15 persons); (b) persons who had been involved in a road traffic accident and retained a memory of the event (13 persons); and, as a control group, (c) patients of an orthopedic ward (15 persons).…”
Section: Introductionsupporting
confidence: 69%
“…Denial of anxiety at a conscious level and, as follows from the research, experiencing it at an unconscious level result in evident disorders of cognitive control. The authors previously quoted the results of research on brain activity in the emotional Stroop test, which indicated that the stronger the interference effect, the greater the dysfunction of the prefrontal cortex (Borkowska, 2006; Coates, 2008; Liu et al, 2015; Song et al, 2017). Quick and accurate decisions are sometimes required from drivers in dangerous situations on the road.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the descriptive data indicated little evidence of a bias in recent survivors, whereas there appeared to be a larger bias towards threat in the PTSD group. Similarly in a Stroop task, interference effects were not correlated with acute stress symptoms in recent road trauma survivors (Coates, 2008). In contrast, using word stimuli (with 1,000 ms presentation time), Bar-Haim et al (2010) reported that in adults under current stress (experiencing rocket attacks), those closest to the attacks demonstrated a bias away from threat words which was correlated with self-reported traumarelated distress.…”
Section: What This Paper Addsmentioning
confidence: 88%
“…It is worth noting that the descriptive data indicated little evidence of a bias in recent survivors, whereas there appeared to be a larger bias towards threat in the PTSD group. Similarly in a Stroop task, interference effects were not correlated with acute stress symptoms in recent road trauma survivors (Coates, ). In contrast, using word stimuli (with 1,000 ms presentation time), Bar‐Haim et al.…”
mentioning
confidence: 99%